Phase formation, microstructures, and mechanical properties of lead-free BNKT ferroelectric ceramics doped with BZZ - Chatchai Kruea-In (2018)
© 2016 Trans Tech Publications, Switzerland. In this research, the effects of bismuth zinc zirconate (BZZ) additive on phase formation, microstructural and mechanical properties of bismuth sodium potassium titanate (BNKT) ceramics were investigated. The BZZ-doped BNKT ceramics were prepared using solid state reaction technique. The pure phase of BZZ-doped BNKT powders were achieved for a calcinations temperature of 850 °C for 4h. The obtained powders were pressed into small pellets and sintered at optimum temperature to form dense ceramics. The XRD analysis of the ceramics shows that all ceramic samples exhibited a pure phase perovskite structure. The bulk densities of samples were about 5.82-6.03 g/cm3 which measured using the Archimedes method. The mechanical properties were measured using micro hardness tester. The microstructural of sintered surface was investigated using scanning electron microscopy (SEM). Average grain size increased with increasing BZZ content. The relations of these results were discussed and compared to the previous works.